Production Et Consommation Du Tchapalo À Abidjan : Typologie Des Brasseuses Et Des Consommateurs - Aka Solange; Dje Koffi Marcellin; Aka Solange; Fokou Gilbert; Doumbia Mohamed; Ahoussi Josiane Marie Stella; Bonfoh Bassirou; Doumbia Mohamed; Ahoussi Josiane Marie Stella (European Scientific Journal, ESJ, 2017)
The tchapalo, traditional Ivorian beer, formerly produced in northern Côte d'Ivoire, has overflowed the geographical limits of its production. Its consumption is becoming more momentum in Abidjan. For a better knowledge of actors and a valorization of this beverage, this work was conducted through a survey of 385 brewers and 77 tchapalo consumers selected in 3 areas of Abidjan. Results showed that tchapalo is produced exclusively by Burkinabe women (45.5%) and the Ivorian women came from northern part of Côte d'Ivoire (53.2%), mainly women of the Lobi ethnic group (90.2%). Tchapalo production was a significant source of income for these women. The biggest consumers of tchapalo came from the Akan ethnic group which represented 52.5% of respondents. Because of its financial accessibility (300 CFA francs per liter), tchapalo is consumed by all socio-economic and professional groups, particularly foremen (41%) and laborers (31.7%). Consumers who found therapeutic principles to the tchapalo represented 54.3% of respondents. Furthermore, over 95% of respondents preferred to consume into tchapalo production area to meet friends and also to maintain fraternity links with brewers. However, 25.7% of consumers chose to consume in a specific tchapalo production area for the taste of the beverage and 25.5% due to welcome that their reserves the producer. Favorite consumption moments were afternoons and evenings.